Situational model of ﬁnancial support for construction in the framework of project implementation in the Russian Federation - D. A. Borisyuk; O. E. Astafyeva (Управление)
The increasing volume of construction ﬁnancing, dictated by the national development goals of the Russian Federation, determines the increased role of rational choice of methods, mechanisms and tools of ﬁnancial support for construction in order to make managerial decisions on the implementation of projects aimed at achieving the targets within the declared national development benchmarks of the Russian Federation. The aim of the study is to summarise and simplify the current methods, mechanisms and tools of ﬁnancial support for construction within the framework of project implementation. A review of the current model of ﬁnancial support for construction in the Russian Federation has been carried out. The main aspects of how to ﬁnance construction have been considered. A brief description of the main conditions of the envisaged mechanisms and instruments of ﬁnancial support for construction has been provided. The analysis conﬁrms the positive trend of the current construction ﬁnancing model in the project implementation, creating conditions to stimulate the economy by reallocating funds to the real sector and providing a variety of tools in choosing construction ﬁnancing methods to make rational management decisions on project implementation. The results of this study can be used by public authorities involved in the allocation and use of funds, ﬁnancial institutions and other stakeholders to prepare management decisions on construction ﬁnancing in project implementation.